2020
DOI: 10.1007/s10669-020-09792-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic real-time risk analytics of uncontrollable states in complex internet of things systems: cyber risk at the edge

Abstract: The Internet of Things (IoT) triggers new types of cyber risks. Therefore, the integration of new IoT devices and services requires a self-assessment of IoT cyber security posture. By security posture this article refers to the cybersecurity strength of an organisation to predict, prevent and respond to cyberthreats. At present, there is a gap in the state of the art, because there are no self-assessment methods for quantifying IoT cyber risk posture. To address this gap, an empirical analysis is performed of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, our methodology is based on mathematical principles and quantitative data. In recent publications on this topic (Radanliev et al 2020b), we discovered that the lack of probabilistic data leads to qualitative cyber risk assessment approaches, where the outcome represents a speculative assumption. Emerging quantitative models are effectively designed with ranges and confidence intervals based on expert opinions and not probabilistic data (Buith 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our methodology is based on mathematical principles and quantitative data. In recent publications on this topic (Radanliev et al 2020b), we discovered that the lack of probabilistic data leads to qualitative cyber risk assessment approaches, where the outcome represents a speculative assumption. Emerging quantitative models are effectively designed with ranges and confidence intervals based on expert opinions and not probabilistic data (Buith 2016).…”
Section: Methodsmentioning
confidence: 99%
“…It also increases the threat posed by cyberattacks such as system compromise, service interruption, and information leakage [5,6]. In particular, the possibility of cyberattacks on drones and self-driving cars along with IoT is expanding beyond the scope of existing cybersecurity areas such as information corruption, leakage, and service interference [7,8]. It is even expanding into areas where safety of human life and property must be guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…Using an autoregressive latent variable model, they found that the emotional responses to attack evolved independently over time. Next, Randanliev et al (2021) compared 12 cyber risk assessment techniques applied to IoT systems. Based on their findings, they described a goal-oriented dependency modeling approach for assessing risk states in IoT systems.…”
mentioning
confidence: 99%